Eight-hours adaptive deep brain stimulation in patients with Parkinson disease. (13th March 2018) - Arlotti, Mattia; Marceglia, Sara; Foffani, Guglielmo; Volkmann, Jens; Lozano, Andres M.; Moro, Elena; Cogiamanian, Filippo; Prenassi, Marco; Bocci, Tommaso; Cortese, Francesca; Rampini, Paolo; Barbieri, Sergio; et al.
Abstract : Objectives: To assess the feasibility and clinical efficacy of local field potentials (LFPs)–based adaptive deep brain stimulation (aDBS) in patients with advanced Parkinson disease (PD) during daily activities in an open-label, nonblinded study. Methods: We monitored neurophysiologic and clinical fluctuations during 2 perioperative experimental sessions lasting for up to 8 hours. On the first day, the patient took his/her daily medication, while on the second, he/she additionally underwent subthalamic nucleus aDBS driven by LFPs beta band power. Results: The beta band power correlated in both experimental sessions with the patient's clinical state (Pearson correlation coefficient r = 0.506, p < 0.001, and r = 0.477, p < 0.001). aDBS after LFP changes was effective (30% improvement without medication [3-way analysis of variance, interaction day × medication p = 0.036; 30.5 ± 3.4 vs 22.2 ± 3.3, p = 0.003]), safe, and well tolerated in patients performing regular daily activities and taking additional dopaminergic medication. aDBS was able to decrease DBS amplitude during motor "on" states compared to "off" states (paired t test p = 0.046), and this automatic adjustment of STN-DBS prevented dyskinesias. Conclusions: The main findings of our study are that aDBS is technically feasible in everyday life and provides a safe, well-tolerated, and effective treatment method for the management of clinical fluctuations. Classification of evidence: This study provides Class IV evidence that for patients with advanced PD, aDBS is safe, well tolerated, and effective in controlling PD motor symptoms.